If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -12 = 6 Reorder the terms: -12 + -3x = 6 Solving -12 + -3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -3x = 6 + 12 Combine like terms: -12 + 12 = 0 0 + -3x = 6 + 12 -3x = 6 + 12 Combine like terms: 6 + 12 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| y-12=28 | | 7(t-4)+5t=4(3t+5)-8 | | 8x^5=18x^4+5x^3 | | 10x-1=59 | | 7m-2m-9=39 | | 11=.5mv^2 | | 168*(37/56)*(7/9) | | 6=4v | | 6x-14=9x+-14-3x | | -4B=16C | | X/4=-x/2-1 | | 10-(13)/(x)=4+(5)/(x) | | t=5(t-32)/9 | | 3(x-2)=-4(3-x) | | 2/5=y-6/y+3 | | g-5/6=-8 | | -3/5y=-50 | | c/4=9/3 | | 26/49*35/44*8/65 | | 26/49*35/44*65 | | Y=5+12x | | 6b+7=-2b+23 | | 3/5x-7=17 | | 3/4n=30 | | -17+1x=11 | | 8x-4x+3x=28 | | 7/8+1/6 | | 4/5x=-20 | | -17+1x=9 | | 2/17x=8 | | (100-4x)/(3)=(5x+6)/(4)+6 | | r-1/2=-3/4 |